Designing Supramolecular Triaminoguanidine‐Based Cobalt(II) Complexes Inspired by Their Zinc(II) Analogs. Issue 9 (22nd February 2022) - Sturm, Lisa; Becker, Marcus; van Leusen, Jan; Oppel, Iris M.
Abstract: Novel cobalt(II) containing compounds of tris ‐(2‐pyridinylene‐ N ‐oxide)triaminoguanidine ligands L 2− are presented: the supramolecular metallocycle [Co6 (OOCMe)3 (NCS)3 L 3 ]4 and the one‐dimensional coordination polymer [Co3 ( μ ‐OOCMe)3 L ]NO3 n . Analog zinc(II) complexes show similar to identical structures that are slightly influenced by different preferences regarding the coordination number. In the polymers, the coordination number is five, which is less common for zinc(II) and rare for cobalt(II). The compounds are characterized by single‐crystal as well as powder X‐ray diffraction, IR spectroscopy, and ESI mass spectrometry. Magnetic measurements revealed predominantly antiferromagnetic exchange interaction between the cobalt(II) centers linked by the triaminoguanidine backbone. Abstract : Novel cobalt(II) containing compounds of tris ‐(2‐pyridinylene‐ N ‐oxide)triaminoguanidine ligands are presented: a supramolecular metallocycle and an one‐dimensional coordination polymer. Analog zinc(II) complexes show similar to identical structures that are slightly influenced by different preferences regarding the coordination number. Magnetic measurements revealed predominantly antiferromagnetic exchange interaction between the cobalt(II) centers linked by the triaminoguanidine backbone.